Does serum anti‐Müllerian hormone levels always discriminate presence of the ovaries in adult bitches? Comparison of two ELISA kits. (28th August 2016) - Pir Yagci, I; Pekcan, M; Polat, IM; Kalender, H; Macun, HC
Contents: Anti‐Müllerian hormone (AMH) is produced in the ovary, and thus, it is an excellent marker of follicle pool in females. Current interest is the clinical use of this parameter as a biomarker to assess presence or absence of an intact ovary and to diagnose ovarian remnant syndrome (ORS) following incomplete ovariohysterectomy (OHE) in bitches. The aim of this study was to evaluate serum AMH concentrations in bitches ( n = 34) before and after OHE using two different commercial ELISA kits, one of which is based on detecting human AMH and the other is based on detecting human AMH and the other specified for canine AMH. Furthermore, serum AMH levels were also measured in six ORS cases to compare the diagnostic utility of the two different ELISA kits. Serum AMH concentrations measured using the human and canine kit prior to and after OHE were 0.32 ± 0.24, 0.006 ± 0.22 ng/ml ( p < .001) and 12.08 ± 22.81, 9.55 ± 15.42 ng/ml ( p = .868), respectively. Thus, the canine‐based kit was not able to reveal the significant drop in serum AMH levels. In conclusion, the human‐based ELISA kits successfully detected the drop in serum AMH concentrations. Reliable results can only be achieved from well‐designed ELISA kits, and AMH levels might be a useful diagnostic tool for the evaluation of presence or absence of ovaries as well as for the detection of ORS cases in bitches.